Vers la déconstruction d’un apprentissage idéologique : Des "représentations-obstacles" dans l’enseignement des langues en France - Gilles Forlot (Recherches en didactique des langues et des cultures)
This article is based on research carried out in several teaching colleges of Northern France and Picardy, where approximately 300 students and teacher trainees were given questionnaires aimed at identifying their sociolinguistic construals. Combining quantitative and qualitative data, the article presents our initial conclusions and explores the various discrepancies between the official objectives of the French educational authorities regarding language teaching and the sociolinguistic stereotypes of those in charge of teaching languages in primary school. We will show the difficulties and sometimes the reluctance of teachers to adhere to the current multilingual orientations for language teaching in France because these orientations challenge the classical approach they themselves went through in their own learning of foreign languages (e.g. vocabulary and grammar based memorisation, drills, etc.). As these sociolinguistic attitudes contribute to linguistic insecurity and the maintenance of monolingual and at times “schizolingual” ideologies in France, we will try to illustrate how teacher training can be helpful in the construction (or the deconstruction) of such construals.